Repression or Civil War? - Besley, Timothy; Persson, Torsten (American Economic Review, 2009)
Perhaps the crowning achievement of mature democracies is the peaceful acceptance of the ballot box as the primary instrument for deciding who should hold power in society. We do not have to go far back in the history of most democratic states, however, to find a distinct role for political violence. Moreover, many inhabitants of the globe still remain at risk of falling prey to widespread violence in the struggle for political office. Forms of political violence differ a great deal. We focus on two important manifestations: repression and civil war distinguished by whether violence is one-sided or two-sided. We present a unified approach to studying these forms of political violence with common roots in poverty, natural resource rents, and weak political institutions. First, we lay out rudimentary model to analyze whether violence will occur and, if so, manifest itself as repression or civil war. Three regimes — peace, repression and civil war — emerge as alternative equilibrium outcomes in the interaction between an incumbent government and an opposition group. Moreover, the theory suggests a natural ordering of these regimes. We then construct empirical measures of repression and civil war, which we map into ordered variables as suggested by the theory. We investigate how the regime depends on economic and political variables, using an ordered logit model defined over the three regimes. Our estimation results indicate a strong correlation between low incomes, weak political institutions and both forms of political violence.